The gender wage gap by education in Italy - Chiara Mussida; Matteo Picchio (Institute for the Study of Labor (IZA), 2012)
This paper studies the gender wage gap by educational attainment in Italy using the 1994-2001 ECHP data. We estimate wage distributions in the presence of covariates and sample selection separately for highly and low educated men and women. Then, we decompose the gender wage gap across all the wage distribution and isolate the part due to gender differences in the remunerations of the similar characteristics. We find that women are penalized especially if low educated. When we control for sample selection induced by unobservables, the penalties for low educated women become even larger, above all at the bottom of the wage distribution.
urn:nbn:de:101:1-201207125614
Keywords: C21; C41; J16; J31; J71; 330; gender wage gap; education; counterfactual distributions; decompositions; hazard function; Lohndifferenzierung; Geschlecht; Weibliche Arbeitskräfte; Dekompositionsverfahren; Italien